Agranulocyosis in Beta Thalassemia Major Patients treated with Oral Iron Chelating Agent (Deferiprone) - Wali, Yasser (OMJ, 2008)
Deferiprone is an oral chelating agent that has been recently shown to reduce cardiac siderosis, but is also known to be associated with serious side effects like agranulocytosis which can be fatal. This report is a single centre experience of 5 cases with severe agranulocytosis in amongst 144 patients (3.47%) of thalassemia major on combined chelation therapy with subcutaneous desferrioxamine and oral deferiprone which is much higher than the previous reports.